Modeling of rotary cement kilns: applications to reduction in energy consumption - Mujumdar, Kaustubh S.; Arora, Amit; Ranade, V. V. (Industrial & Engineering Chemistry Research, 2006)
Rotary cement kilns are used for converting calcineous raw meal into cement clinkers. In this paper, we discuss and evaluate possible ways of reducing energy consumption in rotary cement kilns. A comprehensive one-dimensional model was developed to simulate complex processes occurring in rotary cement Kilns. A modeling strategy comprising three submodels. viz. a model for simulating the variation of bed height in the kiln, a model for simulating reactions and heat transfer in the bed region, and a model for simulating coal combustion and heat transfer in the freeboard region, was developed. Melting and formation of coating within the kiln were accounted for. Combustion of coal in the freeboard region was modeled by accounting for devolatilization, finite-rate gas-phase combustion, and char reaction. The simulated results were validated with the available data from three industrial kilns. The model was then used to understand the influence of various design and operating parameters on kiln performance. Several ways of reducing energy consumption in kilns were then computationally investigated. The model was also used to propose and to evaluate a practical solution of using a secondary shell to reduce energy consumption in rotary cement kilns. Simulation results indicate that varying kiln operating variables, viz. solid flow rate or RPM, can result only in small changes in kiln energetics. Use of a secondary shell over the kiln and energy recovery by passing air through the annular gap between the two appears to be a promising way to achieve significant energy savings. The developed model and the presented results will be useful for enhancing the performance of rotary cement kilns.